Factors describing functioning of management team - Dereškevičiūtė, Edita; Chomentauskas, Gintaras (Psichologija, 2001)
The article presents the complex analysis of variables related with team effectiveness. We applied Input-process-output concept (J. E. McGrath) and P. Vinai, G. Hjelm model. P. Vinai, G. Hjelm's model describes the aspects of organizational functioning that are controlled and influenced by top management team: objectives, performance-output, resources, development and change, management, influence, external relations. In our research 17 top management teams from non-profit non-governmental organizations were assessed.According to our research data following input and process variables related with team effectiveness were determined: financial dependence, activity of members, external relations with sponsors, authorities, strategy, goals, administration and communication. Six factors describing team functioning were defined: I. Purposeful action, II. Communication, III. Conscious competence, IV. Planned activities versus resolution of financial problems, V. External orientation, VI. Structure. Regression analysis allowed to determine variables predicting team effectiveness - they are relations with other organizations (input variable), strategy, goals and communication (group processes).
Keywords: functioning; management team